Bioelectric recording techniques. - Thompson, Richard F.; Patterson, Michael M. (Methods in physiological psychology ;, 1974)
Bioelectric Recording Techniques Part B: Electroencephalography and Human Brain Potentials is part of the multivolume series Methods in Physiological Psychology. The series begins with the treatment of bioelectric recording techniques in three volumes (Parts A, B, and C). Part B deals with electroencephalography (EEG) and peripheral recording of brain events in man. The book is organized into three parts. The first part deals with EEG recording in animals and man, beginning with a historical review of EEG recording and a comprehensive discussion of modern techniques and experimental problems i.